RETRACTED: Biodiversity Loss with Habitat and Risk of New Diseases - Darshit Ram (Biology and Life Sciences Forum)
Biodiversity is the number and variety of organisms found within a specified geographic region. It refers to the varieties of plants, animals, and microorganisms, the genes they contain and the ecosystems they form. Approximately half of Earth’s terrestrial surface is considered to be in a natural or semi-natural condition. It relates to the variability among living organisms on the Earth, including the variability within and between species and that within and between ecosystems. The degradation of nature is among the most serious issues that the world faces, but current targets and consequent actions amount, at best, to a managed decline. Required now are bold and well-defined goals and a credible set of actions to restore the abundance of nature to levels that enable both people and nature to thrive. Human population density strongly correlates with the risk of emergence for all major classes of infectious disease. The maintenance of biodiversity is hypothesised to reduce pathogen prevalence and consequently human disease risk through the dilution effect. However, assuming microbial diversity correlates with that of all other life forms, there may be increased potential for novel pathogens to emerge from biodiverse regions. Here, we present a theoretical framework that exploits the species–area relationship (SAR) to link habitat biodiversity and fragmentation with the exposure to novel infectious diseases.By exploiting ecological theory, it is possible to identify high-risk areas for risk mitigation and mitigation measures that may simultaneously reduce risk and conserve biodiversity, a problem that has previously been described as both conceptually and practically challenging.